ANALISIS PENGGUNAAN MAJAS DALAM ANTOLOGI CERPEN JEMARI LAURIN TAHUN PELAJARAN 2012/2013 - Zuganda, Yobi; Krisna, Eva; Yulianti, Upit (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by the use of figure of speech writers short stories collected in short story anthologies Laurin fingers . Formulation of the problem in this research is